Social representations of migrant women of the same family and of different generations on breastfeeding - Michelle Araújo Moreira; Polliana Santos Ribeiro; Jéssica Suellen Barbosa Mendes Ramos; Marcella Bonifácio Lelles Dias; Juliana Oliveira Castro (Universidade Federal de Santa Maria, 2017)
Aim: to analyze the social representations of female migrants from the same family and from different generations about breastfeeding. Method: a qualitative study based on the Theory of Social Representations, carried out in the city of Ilhéus-Ba, between March and May 2016. The data were obtained by the Free Word Association Test (TALP) with 21 triads selected in the Snowball modality. Software Ensemble of Permettant Programs L'analyze des Évocations (EVOC) was used to analyse the data. Results: for the migrants, breastfeeding is represented as a nutrition practice that contributes to the physical and affective development of the child. The teaching-learning process focuses on the maternal figure and the support network is symbolized by the grandmother, but extended to the parents (or fathers) and husbands. Conclusions: it is necessary to understand the geographical, cultural and social dimensions of breastfeeding in order to offer qualified and humane assistance to migrants.